Innovative Use of Pressure Relieving Foam Based Garment for Lumbar Pressure Sore - Swaroop Johnson Michael; Ravi Kumar Chittoria; Amrutha J.S (International Journal of Biomedical Innovations and Engineering, 2024)
Pressure ulcers, stemming mainly from friction and shear forces, manifest as chronic wounds that worsen over time. They commonly afflict individuals who are bedridden or have limited mobility. Our investigation involved a 62-year-old male with a hypertrophic scar on his back resulting from the excision of a carbuncle. Subsequently, he developed a lumbar pressure sore at the scar site. To address this issue, adjustments were made to his pressure garment, transforming it into a practical solution for alleviating pressure, complemented by the addition of a belt. This modification proved to be both cost-effective and conducive to the patient's adherence to treatment. Enhancing the pressure garment to serve as a pressure-relieving apparatus with the incorporation of a belt not only mitigated the risk of further pressure ulcers but also offered a solution tailored to the patient's needs. This approach, which repurposed existing resources, underscores the importance of innovative strategies in healthcare management. By repurposing the garment, healthcare costs are minimized while maximizing the patient's comfort and compliance. This adaptation not only addresses the immediate concern of pressure ulcer management but also exemplifies a proactive approach to patient care, emphasizing practicality and patient-centered solutions. Moreover, such interventions highlight the significance of individualized care plans tailored to each patient's unique circumstances, fostering optimal outcomes and overall well-being.
Keywords: Pressure ulcer; form; lumbar; pressure garment